효율적인 무 시들음병 저항성 검정법 개발 및 무 품종들의 병 저항성 평가 - 백송이(Song-Yi Baik); 김진철(Jin-Cheol Kim); 장경수(Kyoung Soo Jang); 최용호(Yong Ho Choi); 최경자(Gyung Ja Choi) (Sigmulbyeong yeon'gu, 2010)
To establish the efficient screening method for resistance of radish to F. oxysporum f. sp. raphani, we investigated the development of Fusarium wilt of two radish cultivars, 'Songbaek' (susceptible) and 'Tokwang' (moderately resistant), according to several conditions such as inoculation methods, inoculum concentrations, and dipping periods of radish roots in spore suspension. By infected soil and soil-drenching inoculation methods, Fusarium wilt did not occur on the seedlings of both cultivars. In root dipping inoculation method using cut or non-cut roots of radish plants, the cut roots were easily infected by the pathogen than non-cut roots. And the disease development of two cultivars represented significant difference in non-cut root method. On the other hand, disease severity of Fusarium wilt on radish seedlings according to inoculum concentration increased in a dose-dependant manner, regardless of dipping periods. Using screening method established from the results, the 41 commercial radish cultivars were evaluated the degree of resistance to F. oxysporum f. sp. raphani. Among them, 6 radish cultivars were resistant, 22 cultivars were moderately resistant, and 13 cultivars were susceptible to Fusarium wilt. 무 시들음병에 대한 저항성 검정법을 확립하기 위하여 접종 방법, 침지 시간, 접종원 농도 등의 발병 조건에 따른 '송백무'(감수성)와 '토광무'(중도저항성)의 무 시들음병 발생을 조사하였다. 이병토 접종법, 관주 접종법과 뿌리 침지법 등의 접종 방법에 따른 무 시들음병 발생을 실험한 결과, 이병토 접종법과 관주 접종법에 의해서는 무시들음병이 발생하지 않았다. 뿌리 침지법의 경우, 뿌리 상처 처리구는 무상처 처리구보다 무 시들음병이 더 많이 발생하였으며, 무상처 처리구에서 두 품종의 무 시들음병 발생은 차이를 나타냈다. 뿌리를 포자현탁액에 침지하는 시간(1시간~24시간)에 따른 무 시들음병 발생은 모든 처리구에서 높은 병 발생을 보였으며, 접종 시간이 증가하여도 무 시들음병 발생은 증가하지 않았다. 그러나 포자현탁액의 포자 농도가 증가함에 따라 무 시들음병 발생은 증가하였다. 위의 결과를 이용하여 시판 무 41종 품종의 시들음병 저항성 정도를 검정하였다. 온실에서 14일 재배한 무의 뿌리를 $1.0{×}10^7$ conidia/ml의 포자현탁액에 2시간 동안 침지하여 실험한 결과, 6종 품종(15%)은 저항성, 22종 품종(53%)은 중도저항성 그리고 13종 품종(32%)은 감수성을 보였다.